Comparison study between pilocarpine and tropicamide drops on corneal topography and their effect on IL-6 and TNF-α levels in tear: Pilocarpine and tropicamide drops on corneal topography - Zhang, Yun; Zhao, Jie (Cellular and Molecular Biology, 2022)
Corneal stability is essential for contact lenses and refractive surgery. It seems that paralyzing eye drops or expansion of the ciliary muscle affect the radius of curvature and the strength of the cornea, and this effect is to increase the strength of the cornea during muscle spasm and decrease it in the relaxed state of the muscle. On the other hand, different factors (such as contact lens wear, ocular surface disorders, trauma, dry eye, and immunosuppression) could alter the immune defense mechanisms of the outer eye and permit microorganisms to invade the cornea. Therefore, the present study compared Pilocarpine and tropicamide drop on corneal topography and their effect on IL-6 and TNF-α levels in tear. This prospective study was performed on sixty normal and healthy eyes of sixty volunteers with a mean age of 38.19 years and without any ocular pathology. Volunteers were divided into two groups of thirty. In the first group, corneal topography of both eyes was measured before and 30 minutes after instillation of topical tropicamide 1% in only one eye. The other eye was the control eye, and no drop was given. The same routine was performed in the second group, except that subject received one drop of Pilocarpine 2% in one eye. Statistical comparison between groups for the central corneal power, corneal radius, and corneal astigmatism was performed using paired t-test. IL-6 and TNF-α levels in tear were analyzed using two Luminex commercial assays with Bio-Plex 200TM System (Bio-Rad, Hercules, California, USA). In group 1, no significant changes were found in corneal radius, power, and astigmatism. However, in group 2 subjects who received pilocarpine eye drops, the mean corneal radius value decreased significantly by 0.05 mm. The mean corneal power increased by +0.32 D. There was no significant difference change in corneal astigmatism in both groups. Evaluation of IL-6 levels in tears showed a significant difference between the control and treatment groups (P = 0.041). But no significant difference was observed between the Pilocarpine and the Tropicamide groups (P = 0.761). Evaluation of TNF-α level in tears also showed no significant difference between these groups (P = 0.088). Pilocarpine induced ciliary muscle contraction, which may cause pressure on the corneal limbus and scleral spur, resulting in changes in corneal curvature. But tropicamide eye drop did not affect corneal radius and other corneal parameters, and corneal topography can be carried out after the installation of tropicamide eye drop.